A Study on Self-Compassion and Attachment Styles as the Predictors of Life Satisfaction in Children in Need of Protection - Elif Tuğçe Atalar; Fatih Koca (Children)
Background and Objectives: Societies are obliged to ensure that children in need of protection grow up psychologically, socially, and physically healthy. To achieve that, various practices have been developed. One of these practices is the use of children’s homes sites. Accordingly, this study examined the relationships between the life satisfaction, attachment styles, and self-compassion levels of children in need of protection staying in children’s homes sites. It aimed to determine to what extent variables such as attachment style and self-compassion predict life satisfaction. In addition, whether life satisfaction differs according to gender, age, and the status of having a visitor was examined. Methods: The study sample consisted of 121 children between the ages of 8 and 14 who were staying in children’s homes sites in Istanbul between March and May 2022. The Satisfaction with Life Scale, the short form of the Self-Compassion Scale, the Three-Dimensional Attachment Style Scale, and the Personal Information Form were used with the participants. The researchers used the independent samples t-test, multiple linear regression analysis, Pearson product moment coefficient, and one-way analysis of variance (ANOVA) during the analysis. Results: The findings showed that there was a significant positive relationship between secure attachment style and life satisfaction, anxious–ambivalent attachment, and self-compassion. Also, among the demographic variables, being visited by relatives was found to predict life satisfaction, while there was no relationship between life satisfaction and age and gender. Conclusions: The study findings were discussed within the framework of the literature, and suggestions based on the findings were presented.